Relationship between the Degrees of Itch and Serum Lipocalin-2 Levels in Patients with Psoriasis - Aizawa, Norie (J Immunol Res, 2019)
BACKGROUND: Lipocalin-2 (LCN2), a protein secreted mainly by activated neutrophils, has been associated with neurodegeneration, obesity, and inflammatory responses. Serum LCN2 concentration has been reported elevated in patients with psoriasis, but lower in patients with atopic dermatitis (AD). Spinal astrocyte-derived LCN2 was found to be involved in enhancement of itch in a mouse model of AD. However, the relationship between LCN2 and itch in patients with psoriasis has not been determined. Objective. This study examined the correlation between serum LCN2 levels and the degrees of itch in patients with psoriasis. METHODS: Serum LCN2 concentrations were measured by enzyme-linked immunosorbent assays (ELISA) in patients with psoriasis and AD and in healthy controls. The degree of itch was assessed using a visual analog scale (VAS), and disease severity was determined by measuring psoriasis area and severity index (PASI) and scoring atopic dermatitis (SCORAD). Correlations among serum LCN2 level, VAS, PASI, and SCORAD were analyzed statistically. We further examined the serum LCN levels in psoriasis patients before and after biological treatment. RESULTS: Serum LCN2 concentrations were significantly higher in patients with psoriasis and AD than those in healthy controls. In patients with psoriasis, serum LCN2 concentrations were significantly correlated with VAS, but not with PASI. In contrast, serum LCN2 concentrations did not correlate with VAS or SCORAD in patients with AD. Serum LCN2 levels in psoriasis patients significantly decreased after the biological treatment along with improvement of VAS. CONCLUSION: Serum LCN2 concentration is associated with the degree of itch in patients with psoriasis, suggesting that serum LCN2 may be a useful clinical marker for itch in psoriasis.